2017
DOI: 10.1038/s41598-017-00583-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro developmental ability of ovine oocytes following intracytoplasmic injection with freeze-dried spermatozoa

Abstract: Freeze-drying (FD) is a new and alternative method to preserve spermatozoa in refrigeration or at room temperature. Suitable protection is required to maintain the sperm DNA integrity during the whole process and storage. The aim of this study was to examine the effect of rosmarinic acid and storage temperature on the DNA integrity of freeze-dried ram sperm. In addition, we evaluated the in vitro developmental ability to the blastocyst stage of oocytes injected with freeze-dried sperm. Ram sperm was freeze-dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 56 publications
0
11
1
Order By: Relevance
“…When EDTA FD medium is used, the balance between the amount of ROS and detoxification is compensated by the chelating agent and RA may interfere in its action. It should be noted that in the study of Olaciregui et al [18] in freeze-dried ovine spermatozoa, the percentage of fragmented DNA in EGTA (4.4%) and EGTA-RA (2.9%) was lower than our results, concluding that RA is more efficient when samples are diluted with EGTA and that DNA of rabbit spermatozoa diluted with EGTA is more sensitive to FD process than the ovine equivalent.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…When EDTA FD medium is used, the balance between the amount of ROS and detoxification is compensated by the chelating agent and RA may interfere in its action. It should be noted that in the study of Olaciregui et al [18] in freeze-dried ovine spermatozoa, the percentage of fragmented DNA in EGTA (4.4%) and EGTA-RA (2.9%) was lower than our results, concluding that RA is more efficient when samples are diluted with EGTA and that DNA of rabbit spermatozoa diluted with EGTA is more sensitive to FD process than the ovine equivalent.…”
Section: Discussioncontrasting
confidence: 92%
“…Zhang et al [26] reported that the antioxidants could minimize the detrimental effect of ROS and improve the quality of spermatozoa. Besides, Luño et al [16] showed that RA antioxidant provides a protection against oxidative stress during boar sperm cryopreservation and likewise, Olaciregui et al [18] observed that the addition of RA to EGTA FD medium decreases significantly (p = .003) the percentage of DNA damage in freeze-dried ovine spermatozoa. Lastly, Kodama et al [12] demonstrated that antioxidant treatment in humans with high level of oxidative sperm DNA damage may reduce the extensive oxidative DNA damage.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Rosemary ( Rosmarinus officinalis ) and its extracts, such as rosmarinic acid (RA), are natural antioxidants that show antiproliferative, antiradical and protective properties against oxidant‐induced stress effect (Ho, Wang, Wei, Huang, & Huang, ). In several mammals (Luño et al, ; Olaciregui, Luño, Domingo, González, & Gil, ; Olaciregui, Luño, González, et al, ; Yeni et al, ), including rabbits (Amidi, Pazhohan, Shabani Nashtaei, Khodarahmian, & Nekoonam, ; Domingo, Olaciregui, González, De Blas, & Gil, ), addition of RA in FD or post‐thawing medium (Motlagh et al, ) protected spermatozoa against oxidative stress and improved sperm preservation. In contrast, in a sperm in vitro study, Lv et al () found a decreased intracellular Ca 2+ concentration compromising sperm function after the addition of RA in a dose‐dependent manner.…”
Section: Introductionmentioning
confidence: 99%